A full process optimization of methanol production integrated with co-generation based on the co-gasification of biomass and coal. (15th March 2023) - Li, Shenghui; Sun, Xiaojing; Liu, Linlin; Du, Jian
Abstract: Methanol is an important chemical product with wide application. Due to the high pollutant emission of coal-to-methanol route, feeding mixed raw material of biomass and coal is seen as a promising measure of improvement. More than just focusing on co-gasification unit, this study performs a full process simulation from co-gasification to methanol and cogeneration, aiming at revealing the impact of biomass on process operation and optimizing the key operating parameters. The simulation results imply that coal and biomass co-gasification can improve the utilization of raw materials with more effective gas produced. As an example, the process based on the co-gasification of bituminous coal and straw is specially studied and telling the best operating situation of the whole process. The gasification agent and the critical effects of crude syngas split ratio (SR) and unreacted gas recycle ratio (CR) on the net methanol yield are fully discussed to gain insight into the process. The simulation results show that when the ratio of biomass to coal is 1:1, gasification agent is water steam, SR = 0.36, CR = 0.8, the net methanol production can reach a maximum of 7022.32 kg/h, 241.51% higher than that of merely using coal, producing 37.68% less CO2 than merely using coal. Highlights: Full simulation of biomass and coal to methanol and cogeneration is performed. Effects of factors on syngas components and net methanol yield are analyzed. Side reactions are considered in methanol synthesis process. Combined heat and power process is integrated with production process. CO2 emission reduces by 37.68% in co-gasification to methanol.